2019
DOI: 10.3390/molecules24101957
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Obcordata A from Aspidopterys obcordata on Kidney Stones by Inhibiting NOX4 Expression

Abstract: Obcordata A (OA) is a polyoxypregnane glycoside derived from the Dai medicine Aspidopterys obcordata vines. This study aims to investigate the efficacy of OA on renal tubular epithelial cells exposed to calcium oxalate crystals. We incubated renal tubular cells with 28 μg·cm2 calcium oxalate crystals for 24 h with and without OA, GKT137831, phorbol-12-myristate-13-acetate (PMA), and tocopherol. The MTT [3-(4, 5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide] assay, microscopic examination, flow cytometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 34 publications
1
16
0
Order By: Relevance
“…(Malpighiaceae) is a woody liana and distributes in Hainan and South Yunnan, China (Chen and Funston 2008). The whole plant contained some important biochemical compounds having effects on antiphlogistic and diuresis treatments, which could be used to cure urinary infection and calculus, cystitis, rheumatism, and bone pain, as well as postpartum weak health and children's digestion diseases (e.g., Wu et al 2001;Li et al 2016;Hu et al 2018;Li et al 2019). Plants of this species are important ingredients in some ancient prescriptions of the traditional Dai medicine (State Administration of Traditional Chinese Medicine 2005).…”
Section: Aspidopterys Obcordata; Chloroplast Genome; Dai Traditional mentioning
confidence: 99%
See 1 more Smart Citation
“…(Malpighiaceae) is a woody liana and distributes in Hainan and South Yunnan, China (Chen and Funston 2008). The whole plant contained some important biochemical compounds having effects on antiphlogistic and diuresis treatments, which could be used to cure urinary infection and calculus, cystitis, rheumatism, and bone pain, as well as postpartum weak health and children's digestion diseases (e.g., Wu et al 2001;Li et al 2016;Hu et al 2018;Li et al 2019). Plants of this species are important ingredients in some ancient prescriptions of the traditional Dai medicine (State Administration of Traditional Chinese Medicine 2005).…”
Section: Aspidopterys Obcordata; Chloroplast Genome; Dai Traditional mentioning
confidence: 99%
“… 2018 ; Li et al. 2019 ). Plants of this species are important ingredients in some ancient prescriptions of the traditional Dai medicine (State Administration of Traditional Chinese Medicine 2005 ).…”
mentioning
confidence: 99%
“…Recently, extensive research has explored the effectiveness of generic antioxidants and plant extracts on the alleviation of CaOx crystal damage to epithelial cells, among others L-arginine [46], vitamin E [46], theaflavin [54], taurine [55], corn silk polysaccharides [56], polysaccharides from green seaweed [57], aspidopterys obcordata [58], terminalia arjuna [59], etc. Studies showed that the effects of these antioxidants were beneficial for alleviating oxidative stress on epithelial cells by reducing markers of oxidative damage and increasing cell viability.…”
Section: Antioxidants/plant Extractsmentioning
confidence: 99%
“…As one of the four major ethnomedicines in China [1], Dai medicine dates back more than 2500 years [2] and continues to play an important role in health care in China and many other countries of southeast Asia, especially in the Mekong River valley. Dai antidotes, which include Bin Hao (C. chinense var.…”
Section: Introductionmentioning
confidence: 99%